2002
DOI: 10.1007/s00134-002-1477-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a noninvasive method for cardiac output measurement in critical care patients

Abstract: The noninvasive partial CO(2) rebreathing technique may be an alternative method for CO determination in mechanically ventilated critically ill patients. The rebreathing maneuver alone does not induce changes in CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…To assess the impact of shunt correction and c Hb on the accuracy of CO measurements by IGR we studied different approaches of shunt correction a large cohort of cardiovascular patients with a wide range of haemoglobin levels and cardiac output states giving a fairly realistic representation of a collective to be surveyed by IGR. When comparing the CO measurements without shunt correction (group A) to CMR an acceptable agreement could already be found being similar to the results obtained by other non‐invasive approaches (Murias et al. , 2002; Rocco et al.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…To assess the impact of shunt correction and c Hb on the accuracy of CO measurements by IGR we studied different approaches of shunt correction a large cohort of cardiovascular patients with a wide range of haemoglobin levels and cardiac output states giving a fairly realistic representation of a collective to be surveyed by IGR. When comparing the CO measurements without shunt correction (group A) to CMR an acceptable agreement could already be found being similar to the results obtained by other non‐invasive approaches (Murias et al. , 2002; Rocco et al.…”
Section: Discussionsupporting
confidence: 82%
“…Alternative tests such as partial CO 2 rebreathing which is based on the Fick Principle have been extensively investigated in recent years and revealed diverse findings. While some investigators found a close agreement with thermodilution (Murias et al. , 2002; Rocco et al.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Other tests derived from the Fick principle based on partial CO 2 rebreathing have been extensively investigated in recent years and revealed diverse findings. While some investigators found close agreement with thermodilution [13, 28], others could not confirm these data [10, 14, 29]. Tachibana et al [11] found only poor agreement in spontaneously breathing patients and proposed to restrict this technique to mechanically ventilated patients.…”
Section: Discussionmentioning
confidence: 85%
“…The rebreathing method has also been shown to be accurate and repeatable, not only to Fick 1) but also to thermodilution. 2,18) Conclusion: It is concluded the rebreathing method and velocity-time integral method are excellent noninvasive methods with which to measure cardiac function. They exhibit good correlation, even in these CHF patients with moderate to severe mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%